Bridging Pharmaceutical Chemistry with Drug and Nanoparticle Targeting to Investigate the Role of the 18‐kDa Translocator Protein TSPO. (3rd August 2017) - Iacobazzi, Rosa Maria; Lopalco, Antonio; Cutrignelli, Annalisa; Laquintana, Valentino; Lopedota, Angela; Franco, Massimo; Denora, Nunzio
Abstract: An interesting mitochondrial biomarker is the 18‐kDa mitochondrial translocator protein (TSPO). Decades of study have shown that this protein plays an important role in a wide range of cellular functions, including opening of the mitochondrial permeability transition pore as well as programmed cell death and proliferation. Variations in TSPO expression have been correlated to different diseases, from tumors to endocrine and neurological disorders. TSPO has therefore become an appealing target for both early diagnosis and selective mitochondrial drug delivery. The number of structurally different TSPO ligands examined has increased over time, highlighting the scientific community′s growing understanding of the roles of TSPO in normal and pathological conditions. However, only few TSPO ligands are characterized by the presence of groups that are potentially derivatizable; therefore only few such ligands are well suited for the preparation of targeted prodrugs or nanocarriers able to deliver therapeutics and/or diagnostic agents to mitochondria. This review provides an overview of the very few examples of drug delivery systems characterized by moieties that target TSPO. Abstract : Ligand logistics : Compounds with high affinity and selectivity for the 18‐kDa mitochondrial translocator protein (TSPO) are useful for intracellular drug and nanoparticle targeting. The number of identified structurally distinct TSPO ligands has increased in recent years, highlighting our growing understanding of the roles of TSPO in normal and pathological conditions. This review summarizes some examples of drug delivery systems characterized by TSPO‐targeting compounds.